Numerical simulation of magnetic nano drug targeting to atherosclerosis: Effect of plaque morphology (stenosis degree and shoulder length). (October 2020) - Zhang, Xuelan; Luo, Mingyao; Wang, Erhui; Zheng, Liancun; Shu, Chang
Highlights: Eulerian-Lagrangian coupled FSI technique are adopted to simulate targeted drug delivery to plaque. Delivery efficiency and plaque injury in the process of drug delivery is comprehensively evaluated. Effects of stenosis degree and shoulder length on drug delivery and plaque injury are investigated. The delivery efficiency of particles and plaque injury increase with an increment of stenosis degree. The longer the shoulder length, the higher the delivery efficiency, and the less damage to plaque itself. Abstract: Background and objective : Nanoparticle-mediated targeted drug delivery is a promising option for treatment of atherosclerosis. However, the drug targeting may be affected by multiple factors. Considerable attentions have been focused on the influences of external factors, e.g., magnetic field, drug-loaded particle, but internal factors, e.g., plaque morphology (stenosis degree and shoulder length), have not received any attention yet. Therefore, we investigate the impact of plaque morphology on magnetic nanoparticles targeting under the action of an external field. Method : Numerical simulation, based on Eulerian-Lagrangian coupled Fluid-Solid Interaction, is performed in ANSYS Workbench platform. Blood flow is solved by Navier-Stokes equation, particles are tracked by discrete phase model, and the incorporated effect is obtained by two-way method. Plaques with varying stenosis degrees and shoulder lengths are acquired by manually modifying the geometry of patient-specific. The quantified variables include targeted delivery efficiency (deposition+adhesive strength) of particles and plaque injury characterized by temporal-spatial averaged shear stress ( TAWSS ¯ ) during the process of drug transport, in which the critical deposition velocity is determined by plaques and particles, the DEFINE _ DPM _ BC and User Defined Memory are employed to evaluate whether the particles are deposited, and to store the total number and the adhesive strength of particles deposited on the plaque. Results : Results signify that, with an increment of plaque stenosis degree, the deposition of particle and the adhesive strength between particle and plaque decrease, while the TAWSS ¯ increases. Furthermore, for the same stenosis degree, with the increase of plaque shoulder length, the deposition and the adhesive strength of particle increase, and the TAWSS ¯ decreases. Conclusions : Results demonstrates that the plaque with smaller stenosis degree or longer shoulder length may achieve a better treatment effect in view of the higher targeted delivery efficiency of particles and the lighter shear damage to plaque itself during the process of drug transport.